Republic of Korea : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2014)
This Financial System Stability Assessment report on the Republic of Korea highlights that the Korean economy is experiencing a modest recovery, helped by supportive monetary and fiscal policies and buoyant exports. GDP growth is expected to rebound to 2.8 percent in 2013, and strengthen further to 3.7 percent in 2014, in view of the projected global recovery and a gradual pickup in domestic demand. Inflation has fallen to 0.7 percent in October 2013 from 4.2 percent in 2011. With stronger exports and muted domestic demand, the current account surplus has widened and is expected to reach about 5.5 percent of GDP in 2013.